Astrocyte-specific deletion of peroxisome-proliferator activated receptor-gamma (PPARγ) impairs glucose metabolism and estrous cycling in female mice. - Fernandez, Marina Olga (2017)
Mice lacking PPARγ in neurons do not become leptin resistant when placed on a high-fat diet (HFD). In males, this results in a decrease in food intake and an increase in energy expenditure causing reduced body weight, but this difference in body weight is not observed in female mice. In addition, estrous cycles are disturbed and the ovaries present with hemorrhagic follicles. We observed that PPARγ is more highly expressed in astrocytes than neurons, so we created an inducible, conditional knockout of PPARγ in astrocytes (AKO). The AKO mice showed impaired glucose tolerance and hepatic steatosis that did not worsen with HFD. Expression of gluconeogenic genes was elevated in the livers, as was expression of a number of genes involved in lipogenesis, lipid transport and storage. The AKO mice also showed a reproductive phenotype with reduced numbers of estrous cycles, elevated plasma testosterone, reduced corpora lutea formation, and alterations in hypothalamic and ovarian gene expression. Thus the phenotypes of the astrocyte knockout are very different from those seen in the neuronal knockout suggesting distinct roles for PPARγ in these two cell types.